Diseminasi E-Learning dalam Pemanfaatan Artificial Intelligence (AI) Sebagai Tools Media Pembelajaran pada SMPN 4 Tembilahan Hulu: Dissemination of AI-Based E-Learning Tools in Junior High School 4 Tembilahan Hulu - Anandri, Uya Asy Syuura; Rianto, Bayu; Yunita, Fitri; Melsa; Sudiarti, Yesica Elma; Suryanto; Putra, Misnu Adi (Jurnal Inovasi Pengabdian Masyarakat, 2026)
This service project aims at enabling teachers at SMPN 4 Tembilahan Hulu using planned application of the artificial intelligence in enhancing development of learning media. Under the name of E-Learning Dissemination in the Utilisation of Artificial Intelligence as Learning Media Tools, the presented program will be aimed at a group of 75 pupils and 13 teachers in the school. They included socialisation of AI ideas, intensive workshops, supervised demonstrations, technical support, which incorporated different AI tools, such as ChatGPT and Gemini as scripting and inquiry tools, Gamma and Canva visual design tools, Suno†AI and CapCut audio-visual production tools, and DeepFake and Teachbel Machines. The indicators of success included an increase in the score of technical competence, the creation of eight modules that were focused on AI, and a professional learning community of the teacher. It is projected that this action will enhance the capabilities of teachers to create and develop pedagogically sound, expand learning resources among students, and pose policy change in schools at large that sanction the sustainable use of AI.